CREATIVE COLLISION : ARTIST versus Al - Siti Shahida, Kamel (UNIMAS Publisher, 2023)
The Exhibition of Creativity, Innovation, Technology, and Research in the Arts (eCITRA) is a biannual initiative by the Faculty of Applied and Creative Arts (FACA), Universiti Malaysia Sarawak (UNIMAS). Since its inception in 2005, eCITRA has served as a platform that bridges artistic practice, academic research, and technological innovation, showcasing the evolving dynamics of contemporary art in Malaysia.